First report of Plagiorchis vespertilionis (Müller, 1780), a known zoonotic fluke, with notes on two species of Paralecithodendrium (Platyhelminthes Trematoda) from Myotis sp. and Miniopterus sp. (Mammalia: Chiroptera) in the Philippines - Eduardo, Salcedo L (2021)
Plagiorchis vespertilionis (Müller, 1780) from the mouse-eared bat (Myotis sp.) is described and illustrated based on materials from the Philippines. It is reported for the first time in the country constituting a new locality record for the species. It is differentiated from other species of Plagiorchis declared in the country and also from species from bats in other countries. A pictorial comparison of the general morphology of P. vespertilionis, P. philippinensis, P. potamonides and P. maculosus is provided. Two other species but of the genus Paralecithodendrium namely P. longiforme (Bhalerao, 1926) from the mouse-eared bat and P. ovimagnosum (Bhalerao, 1926) and the bent-winged bat (Miniopterus sp.) are also reported, described, and illustrated based on the present specimens. P. vespertilionis and P. longiforme occurred as concurrent infection in the same host. This is the third account of the two species since these were first recorded in 1928 and last reported in1986.
Keywords: Plagiorchis; Trematoda